An Improved Natural Transformation Protocol for the Cyanobacterium Synechocystis sp. PCC 6803 - Pope, Matthew A.; Hodge, Josh A.; Nixon, Peter J. (Frontiers in Plant Science, 2020)
The naturally transformable cyanobacterium Synechocystis sp. PCC 6803 is a widely used chassis strain for the photosynthetic production of chemicals. However, Synechocystis possesses multiple genome copies per cell which means that segregating mutations across all genome copies can be time-consuming. Here we use flow cytometry in combination with DNA staining to investigate the effect of phosphate deprivation on the genome copy number of the glucose-tolerant GT-P sub-strain of Synechocystis 6803. Like the PCC 6803 wild type strain, the ploidy of GT-P cells grown in BG-11 medium is growth phase dependent with an average genome copy number of 6.05 ± 0.27 in early growth (OD740 = 0.1) decreasing to 2.49 ± 0.11 in late stationary phase (OD740 = 7). We show that a 10-fold reduction in the initial phosphate concentration of the BG-11 growth medium reduces the average genome copy number of GT-P cells from 4.51 ± 0.20 to 2.94 ± 0.13 and increases the proportion of monoploid cells from 0% to 6% after 7 days of growth. In addition, we also show that the DnaA protein, which unusually for bacteria is not required for DNA replication in Synechocystis, plays a role in restoring polyploidy upon subsequent phosphate supplementation. Based on these observations, we have developed an alternative natural transformation protocol involving phosphate depletion that decreases the time required to obtain fully segregated mutants.